Preliminary study on estimation of flow velocity vectors using focused transmit beams. (1st July 2022) - Hasegawa, Hideyuki; Mozumi, Michiya; Omura, Masaaki; Nagaoka, Ryo; Saito, Kozue
Abstract: High-frame-rate ultrasound imaging with plane wave transmissions is a predominant method of blood flow imaging, and methods for estimation of blood flow velocity vectors have been developed based on high-frame-rate imaging. On the other hand, in imaging of soft tissues, such as arterial walls and atherosclerotic plaques, high-frame-rate imaging sometimes suffers from high-level clutters. Even in observation of the arterial wall with a focused transmit beam, it would be highly beneficial if blood flow velocity vectors could be estimated simultaneously. We conducted a preliminary study on the estimation of blood flow velocity vectors based on a multi-angle Doppler method with focused transmit beam and parallel receive beamforming. It was shown that the lowest estimation error was achieved at a steering angle of 25° by simulation. Moreover, velocity vectors with typical velocity magnitudes and directions could be obtained by the proposed method in in vivo measurement of a carotid artery.